Modeling of Filtration Processes with Extended Sources and Homogenization - Sandrakov, Gennadiy (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Methods for modeling dynamic filtration processes with extended sources will be considered. These methods are based on the homogenization of the relevant initial boundary value problems. This approach leads to the description of several filtration modes, the implementation of which depends on the orders of the filtration, transfer, and potentiality coefficients. The problems for describing these modes have constant coefficients and can be solved analytically or numerically. The accuracy of the approximations is also established.